The Role of Parental Wealth and Income in Financing Children's College Attendance and Its Consequences - V. Joseph Hotz; Emily Wiemers; Joshua Rasmussen; Kate Maxwell Koegel (Institute of Labor Economics (IZA), 2018)
This paper examines the influence of parental wealth and income on children's college attendance and parental financing decisions, graduation, and quality of college attended, and whether parental financing affects the subsequent indebtedness of parents and children. We find that higher levels of parents' wealth and income increase the likelihood that children attend college with financial support relative to not attending college, and that parental wealth increases the likelihood that children graduate from college. We show descriptive evidence that parental support for college increases the subsequent level of housing debt that parents hold but does not reduce student debt for children.
Keywords: I2; I22; I24; 330; college attendance and graduation; financing college; effects of parental wealth and income